Determinants of Coffee Shop Business Income in Kintamani District - S. Ayu K. Gitadewi; Luh Gede Meydianawathi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the factors that influence the income of coffee shop businesses in Kintamani District, Bangli Regency, by integrating both traditional and digital factors. Specifically, the research examines the effects of capital, operating hours, selling price, number of customers, and the use of e-money on coffee shop income. Using a quantitative approach, the study applies multiple regression analysis to investigate the relationships between these variables. The findings reveal that both traditional factors such as business capital and operating hours, as well as modern factors like e-money usage, have a significant impact on the income of coffee shop businesses in Kintamani. This research not only fills a gap in the existing literature but also offers practical insights for business actors in the coffee shop industry, particularly in high-tourism areas like Kintamani.